Intermediary workers: Narratives of supervision and support work within the halfway house setting. (December 2020) - Maier, Katharina
Drawing on interviews with halfway house staff, this article provides insight into how these workers conceive of their work and occupational identities within the specific context of the halfway house. Specifically, I examine how halfway house workers seek to differentiate their work and approach to governing former prisoners from that of parole officers. I demonstrate how halfway house workers in this study capitalized on their intermediary position as quasi-state agents, using meso-level complications and struggle to carve out a space in which they felt empowered to carry out multiple, and sometimes conflicting, agendas in their everyday work with halfway house residents.